Structure, dynamics, and related policy issues of fertilizer subsidy in Bangladesh - Ahmed, Raisuddin (International Food Policy Research Institute, 1987)
This chapter analyzes the structure and dynamics of fertilizer subsidy in Bangladesh and a number of related policy issues. Those aspects of the study that concern fertilizer demand, supply, and marketing are covered in other chapters.